Totalitarianism in Yoko Ogawa's The Memory Police - Cahyaningtyas, Lintang; Wahyono, Danu (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2024)
This study discusses about totalitarianism in Yoko Ogawa's The Memory Police. There are four question to be answered in this research: the depiction of totalitarianism in the novel, the cause and effects of totalitarianism in the novel, and the characters' resistance to totalitarianism in the novel. The objective of the study is to find the reflection of totalitarianism on islanders, the depicted cause of totalitarianism, the depicted effects of totalitarianism, and the characters’ resistance to totalitarianism. In analyzing the problem, the writer applies a descriptive qualitative method with sociological approach. The analysis shows the forms of totalitarianism found are terror, absolute control, surveillance, and monopolizing information. The effects of totalitarianism found are loss of trust, intolerance, loss of identity, fear and anxiety, loneliness and isolation, emptiness, trauma and depression. Most of the people calmly accept the reality of the loss of memories, but some fight back. The characters' resistance to totalitarianism found are forming groups, escaping, and making a hiding place. The writer concludes that the Memory Police as a totalitarian government body uses their repressive power to impose forgetfulness and create an oppressive atmosphere. Because of their repressive power, there are many negative effects on the islanders.